Integrated Maternal Health Model for Early Preeclampsia Prevention: A Community Health Center-Based Study in Medan, Indonesia - Aida Fitria; Devi Nallappan; Fina Kusuma Wardani; Dian Zuiatna; M.Crystandy (International Forum of Researchers and Lecturers, 2026)
Preeclampsia remains a major contributor to maternal morbidity and mortality, particularly in developing countries such as Indonesia. Early detection and integrated management at the primary healthcare level are essential to prevent disease progression and improve maternal outcomes. Modifiable risk factors such as maternal obesity, inadequate calcium intake, and poor clinical management contribute significantly to disease progression (WHO, 2021; Zhang et al., 2020). This study aimed to evaluate the effectiveness of an Integrated Maternal Health Model (IMHM) combining risk assessment, nutritional intervention, and clinical management for early prevention and control of preeclampsia in primary healthcare settings. A quasi-experimental cohort study was conducted among 104 pregnant women, consisting of 52 preeclamptic and 52 normotensive participants in community health centers in Medan, Indonesia. Data were collected across four antenatal visits, including blood pressure measurements, proteinuria (dipstick), calcium intake, supplementation adherence, and antihypertensive therapy. Statistical analyses included bivariate and longitudinal tests. The results showed that maternal obesity, history of preeclampsia, and hypertension were significant risk factors. Adequate calcium intake demonstrated a protective effect against preeclampsia (p < 0.05), consistent with recent evidence indicating that calcium supplementation can reduce the risk of preeclampsia by up to 49%. However, calcium supplementation did not significantly influence blood pressure among normotensive pregnant women. Antihypertensive therapy, particularly intensive nifedipine regimens, showed significant differences in blood pressure patterns across visits (p < 0.05). In addition, proteinuria levels significantly decreased over time (p < 0.001), indicating improvement in renal function. In conclusion, the IMHM is effective in improving maternal outcomes through a multi-component approach integrating clinical, nutritional, and monitoring strategies. This model provides a practical and scalable framework for early prevention and management of preeclampsia in primary healthcare settings.